Application of vanadium dioxide in acoustic logging devices - N. A. Semenyuk; Yu. V. Kuznetsova; Vad. I. Surikov; Val. I. Surikov; А. А. Teploukhov (Омский научный вестник)
The study of the elemental composition of samples of vanadium dioxide is used as a thermal sensor in logging complexes after a series of 0, 15, 30, 50 thermal cycles. The influence of thermal Cycling on the elemental composition of the surface of vanadium dioxide and the electrical properties of VO2 in the vicinity of the phase transition is studied. There is change in the electrical properties of the material in the phase transition metal– semiconductor. It is revealed that the value of the electrical resistivity jump at the phase transition is significantly less for the sample, after a series of 50 thermal cycles compared with the original sample.